KEKERASAN TERHADAP ANAK DALAM KONSTRUKSI KORAN TEMPO - Rakhmad, Wiwid Noor (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
The mass media are often accused of discriminatory. Too often considered as one of the factors that influence the rise of violence against children. The truth of the social reality or displayed by the media in reporting crimes against children tend to be partial, because the media actually has a reciprocal relationship with reality itself. On one side of the media is regarded as a mirror of reality and how its operation showing the reality, but the media also do his own interpretation and creates its own reality anyway.Through analysis techniques framing Zhongdang Pan and Gerald M. Kosicki, the study was about to answer the research questions; How does Koran Tempo framing incidence of violence against children and to communicate to the reader in the form of news.